The Quest for Meaning Around Self-Injurious and Suicidal Acts: A Qualitative Study Among Adolescent Girls - Grandclerc, Salomé; Spiers, Solene; Spodenkiewicz, Michel; Moro, Marie Rose; Lachal, Jonathan (Frontiers in Psychiatry, 2019)
Introduction: Suicide and non-suicidal self-injury (NSSI) are major problems in adolescent psychiatry and share numerous clinical characteristics. The principal objective of this study is to describe the subjective experience of adolescent girls and young women who present NSSI and/or suicidal behaviors and to determine the common aspects and the specificities of each experience. Method: This exploratory study is based on a procedure that is qualitative, phenomenological, and inductive. The data were collected from two semi-structured interviews each of 18 girls and young women aged 12 to 21 years, who were receiving care from a psychiatrist specializing in adolescents and who at least once had harmed themselves by NSSI or attempted suicide, or both. The thematic data analysis was performed by applying the methods of interpretative phenomenological analysis. Results: The results are described around four superordinate themes: relationships with the self, with others/otherness, with the body, and with death; they are then subdivided into 13 themes. Several themes appeared common to both types of behavior, especially the relational dimension of self-harming acts. The process of separation-individuation seems complex for these youth. Conclusion: The results underline the relational aspects of the self-harming behavior (NSSI or suicidal) among adolescent girls. These aspects also appear to be expressed in the family sphere, the social sphere, in contact with peers, and also at a societal level when the community no longer addresses adolescents’ difficulties. When the process of subjectification does not appear to reach completion, self-aggressive behavior is seen as an ultimate attempt to regain a feeling of autonomy.